Research into milk homogenization in the pulsation machine with a vibrating rotor - Samoichuk, Kyryl; Самойчук, Кирило Олегович; Самойчук, Кирилл Олегович; Kiurchev, Serhii; Кюрчев, Сергій Володимирович; Кюрчев, Сергей Владимирович; Oleksiienko, Vadym; Олексієнко, Вадим Олександрович; Алексеенко, Вадим Александрович; Palianychka, Nadiia; Паляничка, Надія Олександрівна; Паляничка, Надежда Александровна; et al. (My University, 2016)
EN: Nowadays it is difficult to find a dairy production scheme where homogenization would not be used [1]. Homogenization improves the taste and sensory internals of milk, increases its viscidity and stability, contributes to a better assimilability of the smaller particles of milk fat, etc [2]. Modern machineswhich are used for milk homogenization often do not meet modern requirements of quality and energy-savings [3]. Valve homogenizers are the most widespread. They are notable for the highest quality rates of dispersion of milk emulsion, but their energy consumption exceeds 7 kW/t [4, 5]. Despite low energy consumption vacuum, ultrasonic and rotor homogenizers do not provide high degree dispersing [6–8]. On the contrary the ultra-high-pressure homogenizers and microfluidizers provide high degree dispersing of the processed emulsion but have superhigh energy consumption [9, 10]. Taking into account stated above and modern tendency to energy saving technologies implementation the actual problem of the dairy industry is to design machines for milk homogenization with quality rates of dispersion of milk emulsion on a level of valve machines but with lower energy consumption. UK: Обґрунтовано вплив основних кінематичних і конструктивних параметрів пульсаційного гомогенізатора з ротором, що вібрує, на середнє прискорення емульсії в отворах переривника. Встановлено залежність середніх розмірів жирових кульок молока від прискорення емульсії в переривнику апарата та частоти обертання й амплітуди вібрації ротора. Визначені дисперсні характеристики молока після гомогенізації. RU: Обосновано влияние основных кинематических и конструктивных параметров пульсационного гомогенизатора с вибрирующим ротором на среднее ускорение эмульсии в отверстиях прерывателя. Установлена зависимость средних размеров жировых шариков молока от ускорения эмульсии в прерывателе аппарата и частоты вращения и амплитуды вибрации ротора. Определенные дисперсные характеристики молока после гомогенизации.
Keywords: гомогенізація молока; гомогенізатор; пульсаційний апарат з ротором, що вібрує; гомогенизация молока; гомогенизатор; пульсационный аппарат с вибрирующим ротором